The Influence Of Fomo On Purchase Intention Through Brand Engagement On Tiktok Among Generation Z Decoding Fomo: Social Anxiety And Purchase Intention Through Brand Engagement On Tiktok - Dilla, Savira Cahya; Wibowo, Moersito Wimbo; Ahya, Awaludin (UNIVERSITAS PAKUAN, 2025)
This study aims to analyze the impact of social anxiety due to Fear of Missing Out on purchase intention through consumer brand engagement on TikTok among Generation Z. The study involved 250 respondents who actively use TikTok and have online shopping experience. Using a quantitative approach and multiple regression analysis, the results indicate that social anxiety significantly affects purchase intention, both directly and indirectly through brand engagement. The regression model explains 58.2% of the variance in purchase intention. These findings provide insights for marketers to develop more interactive and psychologically driven marketing strategies to enhance brand engagement and purchasing decisions.